A rare case of primary cutaneous malignant perivascular epithelioid cell tumor and review of the literature. (3rd October 2022) - Cornell, Georgeanne; Jiang, Betty; Ghaferi, Jessical
Abstract: A 77‐year‐old female presented with a 6‐month history of a 2‐cm pink exophytic tumor on the right anterior shin, which had grown rapidly and began to bleed over the last 4 weeks. A shave biopsy showed a dermal proliferation of epithelioid spindled cells, arranged in nests and trabeculae associated with thin‐walled capillary vessels. The cells showed pleomorphic nuclei with vacuolated nuclear chromatin and occasional prominent nucleoli. Mitotic figures (7/10 high‐power fields [HPFs]), including atypical forms, were present in the specimen. Immunohistochemical staining was negative for SOX10 and stained positive for MiTF. The histopathologic findings were consistent with a malignant perivascular epithelioid cell tumor (PEComa). A malignant PEComa is a rare entity of mesenchymal‐derived cells with both melanocytic and myocytic differentiation. A PEComa is considered to be malignant by fulfilling two of the following criteria: size greater than 5 cm, vascular invasion, necrosis, mitotic figures greater than 1 per 50 HPF, infiltrative growth pattern, high nuclear grade, and hypercellularity. PEComas show immunohistochemical positivity to myocytic markers such as SMA, pan‐muscle actin, muscle myosin, calponin, and h‐caldesmon as well as melanocytic markers such as HMB‐45, Melan‐A, tyrosinase, and MiTF.